2015
DOI: 10.3386/w20879
|View full text |Cite
|
Sign up to set email alerts
|

Why is Pollution from U.S. Manufacturing Declining? The Roles of Environmental Regulation, Productivity, and Trade

Abstract: Between 1990 and 2008, air pollution emissions from U.S. manufacturing fell by 60 percent despite a substantial increase in manufacturing output. We show that these emissions reductions are primarily driven by within-product changes in emissions intensity rather than changes in output or in the composition of products produced. We then develop and estimate a quantitative model linking trade with the environment to better understand the economic forces driving these changes. Our estimates suggest that the impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…Based on the above studies, to keep it simple but without loss of generality, we construct the conversion factor which is the inverse ratio of city‐ and sub‐sector‐specific TFP over the provincial‐sector‐specific TFP. Martin () and Shapiro and Walker () also build their empirical analysis on a similar assumption. The apparent advantage here is that we have all the TFP measures needed for calculating those conversion factors coming from ASIFs dataset and China's Urban Statistical Yearbooks…”
Section: Decomposition Of Carbon Dioxide Emissions In Chinese Citiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the above studies, to keep it simple but without loss of generality, we construct the conversion factor which is the inverse ratio of city‐ and sub‐sector‐specific TFP over the provincial‐sector‐specific TFP. Martin () and Shapiro and Walker () also build their empirical analysis on a similar assumption. The apparent advantage here is that we have all the TFP measures needed for calculating those conversion factors coming from ASIFs dataset and China's Urban Statistical Yearbooks…”
Section: Decomposition Of Carbon Dioxide Emissions In Chinese Citiesmentioning
confidence: 99%
“…All else being equal, if the manufacturers in an industry adopt more efficient environmentally friendly production methods and improve management quality, it will induce a negative technique effect, thus reducing energy consumption and CO 2 emissions per unit of economic activity within this industry. Shapiro and Walker () find that the observed decrease in nitrogen oxide emissions (NO x ) in the USA during the period of 1990–2008 is more attributable to falling pollution per unit of output within industries at a more disaggregated level, suggesting the existence of a technique effect in those industries. A study focusing on China by Zhang () finds that the changes in input mix, sector energy intensity, fuel mix and carbon intensity of fuels can offset the increasing trade‐induced carbon emissions in twenty‐six sectors including agriculture, mining, manufacturing and service industries.…”
Section: Survey Of Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…For instance, some international agreements (e.g., the Montreal Protocol on Substances that Deplete the Ozone Layer) fix an exogenous ceiling on specific polluting concentrations. Shapiro and Walker (2015) found that the increasing stringency of US environmental regulation accounted for three quarters of the 60% decrease in pollution emissions (e.g., nitrogen oxides, particulate matter, sulfur dioxide, and volatile organic compounds) from US manufacturing in the period from 1990 to 2008. In general, both price and quantity forms of control can solve allocation problems and there is no a priori criterion to favor one instrument over the other [Weitzman (1974)].…”
Section: Introductionmentioning
confidence: 99%